Women’s Health, Indoor Air Pollution (IAP) and Sustainable Energy - Dabral Sumit; Joshi Janak; Bhatt Bindu (International Journal of Research in Chemistry and Environment (IJRCE), 2016)
Air pollution is usually thought about ambient or outdoor air pollution – smokestacks spouting dark grey clouds of toxic smoke into the atmosphere or choking exhaust from vehicles and industrial effluents. It is not surprising, then, that whatever pollution monitoring is done takes place within the ambient environment. It is a common belief that while indoors, one is safe from harmful pollutants. On the contrary, the scientific evidence has shown that indoor air at homes can be more seriously polluted than outdoor air in industrialized cities. In fact, the United States Environmental Protection Agency estimates that the air indoors can be two to five times more polluted than the air outside. A silent majority of the population, namely poor women and children, continue to suffer from air pollution in the indoor environment. Women and children in low socio-economic groups, especially in rural areas and informal urban settlements and in the developing countries are breathing air that is highly polluted. It is estimated that, each year, 4.3 million premature deaths, mainly of women and children, are associated with inhaling toxic fumes from fuels such as wood, animal waste, and charcoal used for cooking and heating. Nearly a quarter of all premature deaths due to stroke and 15 percent of those due to ischemic heart disease as well as one-third of those from chronic-obstructive lung disease in low- and middle-income countries, are thought to be due to exposure to household air pollution. In children, it almost doubles the risk of pneumonia. It is considered as oldest pollution source in human history by definition with the greatest health consequence remains invisible or ignored. The impact of this environmental exposure has been relatively neglected by research and policy makers. Good quality of air is just as vital as safe water or food for life. Hence, the study intends to explore links between women’s health, indoor air pollution and path toward achieving sustainable development.